Pendekatan Integralistik Dalam Harmonisasi Konflik Tenurial Di Kawasan Hutan Berdasarkan Perspektif Ekonomi Pancasila - Dita Perwitasari; Tamsil; Indri Fogar S; Mahendra Wardhana (Universitas Negeri Semarang, 2026)
Land tenure conflicts in Indonesian forest areas persist as a complex issue involving overlapping claims between the state, corporations, and local communities, often leading to social injustice, environmental degradation, and economic inequality. This study explores an integralistic approach rooted in Pancasila's economic perspective, emphasizing the principles of gotong royong (mutual cooperation), social justice, and familial spirit to harmonize these conflicts. Employing normative legal research with a conceptual and philosophical approach, the analysis draws on literature reviews of recent studies (2015–2025) on agrarian reform, social forestry, and tenure resolution policies. Findings reveal that conventional approaches prioritizing state control and corporate interests exacerbate conflicts, while Pancasila's economic system—promoting equitable resource distribution for collective prosperity—offers a holistic framework for resolution through mechanisms like social forestry, participatory mediation, and equitable land redistribution. This approach not only resolves tenure disputes but also fosters sustainable forest management, enhances community welfare, and supports national food security. The research contributes to global society by providing a model of value-based conflict resolution that integrates economic democracy with environmental sustainability, applicable in multicultural developing nations facing similar resource conflicts.